Significance of intramedullary T2* signal voids in the magnetic resonance imaging of paraplegic deep pain-negative dogs following intervertebral disc extrusion at short-term follow-up - Clark, Robert; Ferreira, Amy; Behr, Sebastien (Frontiers in Veterinary Science, 2023)
Dogs presenting as paraplegic without nociception due to a thoracolumbar intervertebral disc extrusion provide a difficult decision to both the clinician and the owner. The prognosis when performing surgical decompression remains guarded. Aside from significant extradural compression, these dogs often have significant secondary spinal cord injury which has shown to be an important factor in determining both the likelihood of developing progressive myelomalacia and the return to ambulation. This is a retrospective, observational, single centre study including 82 dogs presenting as paraplegic with absent nociception diagnosed with an